(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To compare the treatment outcome of combination of corticosteroid injection with physiotherapy and physiotherapy alone in patients with adhesive capsulitis in term of shoulder pain and disability index (SPADI) score. Methods: This was a randomized controlled trail conducted using probability simple random sampling technique at the Department of Orthopedic Surgery, Fatima Jinnah Medical University, Sir Ganga Ram Hospital, and King Edward Medical University, Mayo Hospital Lahore from February 2106 to September 2018. All patients of frozen shoulder fulfilling the inclusion criteria were randomly divided into two groups as A & B by lottery method. Pre treatment shoulder pain and disability index (SPADI) was calculated. Group-A was given intra-articular corticosteroid and physiotherapy while group-B received only physiotherapy. Post intervention SPADI score of both groups were calculated 6-week after the treatment on follow-up in the out-patient department. Independent sample t-test was used to compare the SPADI score between two groups and p-value <0.05 was taken significant. Results: Out of the total 80 patients in both groups(40 in each group), the mean age of the patients in group-A was 45.18±7.29year while in group-B it was 43±7.43year. The mean duration of the symptoms in group-A was 3.29±1.62month while in group-B it was 3.25±1.69year. In group A, SPADI score at baseline was 71.68±7.67 while in group B it was 71.88±6.74 (p-value=0.902). After 6-week SPADI score in group A was 36.7±5.28 while it 39.78±5.89 in group B. It was found statistically significant in both group (p value 0.016). For age and gender stratification with SPADI score at baseline and 6-week we found statistically significant difference. Conclusion: Combination therapy of corticosteroid injection with physiotherapy was effective treatment in patients with adhesive capsulitis in pain relieve and reduction in disability index.